1989
DOI: 10.3109/10826088909047272
|View full text |Cite
|
Sign up to set email alerts
|

Telescoping of Alcoholism in Women Alcoholics

Abstract: The accelerated progression of alcoholism, or telescoping, was examined among women alcoholics. Three aspects of telescoping in women were examined: the age of onset of four landmark symptoms, the number of years between landmark symptoms, and the number of symptoms occurring within each interval between landmarks. Women alcoholics were found to report a significantly shorter interval between the age at which they first began experiencing alcohol-related problems and the time they sought treatment than did mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
121
7
8

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(149 citation statements)
references
References 10 publications
12
121
7
8
Order By: Relevance
“…31 However, given gender-related biases in these populations, 11,32 these findings cannot be generalized to other women. Therefore, for this review, data from the most generalizable studies relating to each subtopic were selected and reviewed.…”
Section: Study Selection and Data Extractionmentioning
confidence: 86%
“…31 However, given gender-related biases in these populations, 11,32 these findings cannot be generalized to other women. Therefore, for this review, data from the most generalizable studies relating to each subtopic were selected and reviewed.…”
Section: Study Selection and Data Extractionmentioning
confidence: 86%
“…For substance use disorders, including alcohol, opioid, and cannabis dependence, females advance more rapidly from use to regular use to first treatment episode than do their male counterparts (Dawson, 1996;Hernandez-Avila et al, 2004;Johnson et al, 2005;Orford and Keddie, 1985;Piazza et al, 1989;Randall et al, 1999). In addition, when they enter treatment, in spite of fewer years of use and smaller quantities of substances used, their substance abuse symptom severity is generally equivalent to that of males (Hernandez-Avila et al, 2004;Piazza et al, 1989;Randall et al, 1999). Even with fewer years of substance use, at treatment entry, females average more medical, psychiatric, and adverse social consequences of their substance use disorders than males.…”
Section: Introductionmentioning
confidence: 99%
“…The accelerated development of addiction in females, the so-called "telescoping effect" (T.E. ), was first described in alcoholism by Lisansky 33 and confirmed by Piazza et al 34 , as well as observed in opioid addiction by Anglin et al 35 . Other authors have also described T.E.…”
Section: Course and Evolutionmentioning
confidence: 94%
“…in alcoholism occurs in the interval between the age at which they first experienced alcohol-related problems and the time they sought treatment 34,39,40 . Lewis et al 41 described that women start to drink later than men but develop problems in the first 2 years of alcohol use.…”
Section: Course and Evolutionmentioning
confidence: 99%